2010
DOI: 10.18433/j3n88n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Of Selective TRPM8 Ligands And Their Structure Activity Response (S.A.R) Relationship

Abstract: -Purpose. Transient receptor potential melastatin-8 (TRPM8) is an ion channel expressed extensively in sensory nerves, human prostate and overexpressed in a variety of cancers including prostate, breast, lung, colon and skin melanomas. It is activated by innoxious cooling and chemical stimuli. TRPM8 activation by cooling or chemical agonists is reported to induce profound analgesia in neuropathic pain conditions. Known TRPM8 agonists like menthol and icilin cross-activate other thermo-TRP channels like TRPV3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 42 publications
2
54
0
Order By: Relevance
“…Both ligand-gated and voltagegated channels are inhibited by menthol (IC 50 5 297 mM for Na 1 channels and IC 50 5 125 mM for Ca 21 channels in dorsal horn neurons) (Pan et al, 2012). Moreover, the effective concentrations observed in the current study were found to be comparable with menthol concentrations sufficient to activate TRPM8 channels, with EC 50 values ranging between 67 and 196 mM (Sherkheli et al, 2010) in X. laevis oocytes. However, menthol also nonselectively activates TRPV3 (EC 50 5 20 mM) and inhibits mouse TRPA1 (IC 50 5 68 mM) (Macpherson et al, 2006).…”
supporting
confidence: 57%
“…Both ligand-gated and voltagegated channels are inhibited by menthol (IC 50 5 297 mM for Na 1 channels and IC 50 5 125 mM for Ca 21 channels in dorsal horn neurons) (Pan et al, 2012). Moreover, the effective concentrations observed in the current study were found to be comparable with menthol concentrations sufficient to activate TRPM8 channels, with EC 50 values ranging between 67 and 196 mM (Sherkheli et al, 2010) in X. laevis oocytes. However, menthol also nonselectively activates TRPV3 (EC 50 5 20 mM) and inhibits mouse TRPA1 (IC 50 5 68 mM) (Macpherson et al, 2006).…”
supporting
confidence: 57%
“…3). Therefore, we performed similar experiments using a more specific TRPM8 agonist, WS-12 (10). WS-12 (30 µM) augmented the currents in both HSC3 and HSC4 cells, an effect that was powerfully inhibited by RQ in each cell line (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Although it seems possible that TRPM8 might also be involved in the pathophysiology of oral cancer cells, its expression and functional significance in such cells remain unclear. Unfortunately, in tissues expressing other TRP members the less-selective pharmacological tools currently available have limited the ability of basic research to identify pathophysiological roles for these TRPs (3,10).…”
Section: Introductionmentioning
confidence: 99%
“…For TRPM8 activation by WS-12 (a menthol analog; Ma et al, 2008;Sherkheli et al, 2010), intracellular calcium mobilization was measured using a functional drug screening system (FDSS 6000; Hamamatsu, Shizuoka, Japan) with the Fluorometric Imaging Plate Reader Calcium Assay Kit (Molecular Devices, Sunnyvale, CA). Human embryonic kidney 293 (HEK-293) cells were stably transfected with a human transient receptor potential melastatin (TRPM8) receptor construct (accession number NM_024080).…”
Section: Methodsmentioning
confidence: 99%